Hemlock & Silver - Kingfisher, T. (New York : Tor, Tor Publishing Group, 2025)
"From New York Times bestselling and Hugo Award-winning author T. Kingfisher comes Hemlock & Silver, a dark reimagining of "Snow White" steeped in poison, intrigue, and treason of the most magical kind Healer Anja regularly drinks poison. Not to die, but to save- seeking cures for those everyone else has given up on. But a summons from the King interrupts her quiet, herb-obsessed life. His daughter, Snow, is dying, and he hopes Anja's unorthodox methods can save her. Aided by a taciturn guard, a narcissistic cat, and a passion for the scientific method, Anja rushes to treat Snow, but nothing seems to work. That is, until she finds a secret world, hidden inside a magic mirror. This dark realm may hold the key to what is making Snow sick. Or it might be the thing that kills them all"--
Keywords: Fantasy fiction; Novels